Performing rapid autopsy for the interrogation of HIV reservoirs. (1st June 2020) - Rawlings, Stephen A.; Layman, Laura; Smith, Davey; Scott, Brianna; Ignacio, Caroline; Porrachia, Magali; Concha-Garcia, Susanna; Hendrickx, Steven; Kaytes, Andy; Taylor, Jeff; Gianella, Sara
Abstract : N/A: Rapid autopsy at the end of life in people with HIV (PWH) permits the preservation of valuable tissue specimens for subsequent study of HIV reservoirs. At our institution, we have developed a cohort of PWH who consent to a rapid autopsy to gather a wide range of fluids and tissues with the goal of advancing HIV cure research. The protocol for successfully performing these autopsies has required careful thought and development over months and years. We have now successfully performed six rapid autopsies and detail here our steps to build the study cohort, train and staff a team of more than a dozen personnel, and process and preserve hundreds of samples from each autopsy. Abstract : Supplemental Digital Content is available in the text